Psychological intervention priorities according to perinatal women who experienced suicidal thoughts and perinatal mental health professionals: a Q-methodology study - Reid, Holly E.; Pratt, Daniel; Edge, Dawn; Wittkowski, Anja (Frontiers in Psychiatry, 2023)
Introduction: Suicide is the leading direct cause of maternal death in the year following birth and the second leading cause during pregnancy, in the UK and Ireland. Currently no evidence-based psychological interventions exist specifically designed to reduce mothers' suicidal experiences during the perinatal period. Reducing suicidal ideation and behaviour in mothers is a priority to prevent deaths and lessen the distress felt by mothers and their families. As Q-methodology measures the consensus and disagreement between individuals on a given topic, the current study used Q-methodology to elicit the priorities for a future psychological intervention aimed at reducing suicidal ideation and behaviour during the perinatal period, from the collective perspectives of both mothers and professionals.Method: As part of this Q-methodology study, we developed a Q-set of 75 statements pertaining to possible elements of a psychological intervention that might help reduce a mother's suicidal ideation and behaviour during the perinatal period. Mothers and professionals were recruited via perinatal mental health services and social media advertisements.Results: Twenty-one mothers and 11 perinatal mental health professionals ranked each Q-set statement depending on its perceived importance in developing a new intervention. A centroid factor analysis was conducted and two factors, which accounted for 42% of the overall variance, were identified: Factor 1 'supporting the mother to create distance between herself and the appeal of suicide' and Factor 2 'establishing positive connections with the therapist, the baby and motherhood'. All participants believed that developing plans to keep the mother safe from suicide was the most important aspect for inclusion in a future intervention. Participants who loaded onto Factor 1 also prioritised supporting mothers to learn more about triggers for their suicidal ideation and behaviour. Ensuring a robust therapeutic alliance was more important for those who loaded onto Factor 2.Conclusions: This is the first study using Q-methodology to explore the psychological intervention priorities of mothers and professionals. Findings indicate clear priorities in terms of planning and coping during a crisis, endorsed by all participants, and provide an initial step in the development of a new perinatal suicide prevention intervention.